Karakteristik Menara Pendingin dengan Bahan Isian Ijuk - Susanto Johanes (Faculty of Engineering, Universitas Gadjah Mada, 2010)
In this study the characteristic of a water cooling tower by using the palm fibre as thepacking material have been investigated experimentally. The experiments were carried out in arectangle glass tower of 81 cm2 cross sectional area and 100 cm height. The packing used wasconstructed of 8 palm-fibre ropes (of about 0,6 cm diameter), zigzag vertically placed above thestainless steel support on the tower bottom. Its type has 28,3.10-4 kg weighs of rope every m3volume of the packing.The experimental results show that the increasing of the water inlet temperature and thepacking height cause the increasing of the tower characteristic. Mean while, the increasing ofthe water/air mass flow rate ratio causes the decreasing of the tower characteristic. The towercharacteristic is as a function of the investigated variables which expressed as:NTU = 3,35.10-3 (m w /m a )-0,995 (Z)0,5050 (T wi )1,1643with the relative error of 5,5%.This equation is valid for the range of variables, as m w /m a which is ranged from 4,46 to9,48, Z which is ranged from 30 to 90 cm, T wi which is ranged from 50 to 60 oC. The meaneffectiveness of the heat transfer were calculated to be 25,9%.Keywords: Cooling tower, characteristic, effectiveness, palm-fibre ropes.